(untitled) (The Review of Diabetic Studies, 2025)
Background & aim: Therefore, the current study aimed to determine the histological effects of copper sulfate on the stomach, study the long-term effects of copper sulfate, and use different concentrations of copper sulfate to understand the effect on the stomach tissue structures. Materials and Methods: This study was conducted at the Animal House of the College of Veterinary Medicine, Tikrit University, during the period from September 1 to October 1, 2024. Forty-five rats were used for the current study. They were divided into two main groups: the control group and the copper sulfate groups. The rats were given 8 mg / kg B.W / day of a copper sulfate solution dissolved in distilled water. Results: Histological examination of the transverse sections of all groups dosed with copper sulfate showed many tissue lesions represented by many of simple columnar cells appear to have sloughed off in the gastric lumen. The gastric glands in the basal lamina have undergone shrinkage from the surrounding basement membrane. There is also atrophy of the cells lining these glands, and debris from sloughed epithelial cells is present in the lumen of the tubular glands. also, the loose connective tissue around the glands and gastric pits contained fibroblasts and scattered leukocytes. Masses of necrotic secretory cells were also found and the sections showed degeneration of several chief cells, and cervical mucosal cells Conclusions: it is concluded that copper sulfate has very harmful effects on gastric tissues, including the destruction of the epithelial lining and gastric glands, and that the longer the exposure period to copper sulfate, the more severe the tissue effects.